Bankowość muzułmańska – podłoże ideologiczne oraz religijne - Kasiak, Marek (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2016)
In the course of the years of economical crisis that have spilt all over the world, many investors have started to look for ways for more secure investments – other than those offered by traditional banking. Hence, there has been noted rising popularity of Islamic Banking. The purpose of this paper is to provide a closer look on the Islamic Banking. To explore such difficult topic, first of all, it is necessary to present the ideological foundation of the Islamic culture and the Islamic Banking solely. The paper provides a brief description of an ideological and religious background of the Islamic Banking phenomenon
Keywords: bankowość; szariat; bankowość islamska; haram; riba; gharar